2007
DOI: 10.1002/jmri.20808
|View full text |Cite
|
Sign up to set email alerts
|

Collagen structure: The molecular source of the tendon magic angle effect

Abstract: This review of tendon/collagen structure shows that the orientational variation in MRI signals from tendon, which is referred to as the "magic angle" (MA) effect, is caused by irreducible separation of charges on the main chain of the collagen molecule. These charges are held apart in a vacuum by stereotactic restriction of protein folding due in large part to a high concentration of hydroxyproline ring residues in the amino acids of mammalian collagen. The elevated protein electrostatic energy is reduced in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(137 citation statements)
references
References 90 publications
7
124
0
Order By: Relevance
“…The average correlation time of cell water would be expected to decrease from 27 ps to several times slower than the correlation time of bulk water (1.74 ps). This degree of slowing is in the reported measured range for monolayer water coverage of tendon/collagen Rahal 2007 andCameron andFullerton 2008).…”
Section: Physical Measured Properties Of Bulk and Non-bulk Water Fracsupporting
confidence: 58%
“…The average correlation time of cell water would be expected to decrease from 27 ps to several times slower than the correlation time of bulk water (1.74 ps). This degree of slowing is in the reported measured range for monolayer water coverage of tendon/collagen Rahal 2007 andCameron andFullerton 2008).…”
Section: Physical Measured Properties Of Bulk and Non-bulk Water Fracsupporting
confidence: 58%
“…As shown previously, 19 SHM theory predicts that each water molecule departing from a given water category causes equal changes in tendon properties but with different values for other water compartments. It is predicted that relative diameter d / d 0 , relative length l / l 0 , relative volume V / V 0 , and density will have segmental-linear properties.…”
Section: Iib6 Derivation Of Linear Shm Segmental Equations For Anamentioning
confidence: 83%
“…The SHM makes predictions traceable to the molecular structure of the collagen molecule and was previously validated by DSC, 19 NMR, 20 MRI, 19 centrifugation dehydration, 21 and other methods as recently reviewed. 22 Initially, the SHM model hypothesized significant free energy differential between water fractions that allows depopulation of water compartments in sequence, but more recently, DSC studies have confirmed this point.…”
Section: Ia Validation Of Molecular Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of water with collagen fibres (e.g., Fullerton and Rahal 2007) and other molecular chains (such as actin and microtubules) has been investigated extensively. Pollack (2001) reports that transport of water along filamentous structures is partly caused by the transport of solutes, which carry with them a "cloud" of structured water.…”
Section: Introductionmentioning
confidence: 99%